In Silico Prediction of 3D Structure of Pectatelyase from Fusarium oxysporum f. sp. lycopersici - pige, Ramesh K.V2; Vikram A, Raghavendra Rao B, Manojkumar H. Nagasam (Recent Research in Science and Technology, 2011)
In Silico Prediction of 3D Structure of Pectatelyase from Fusarium oxysporumÃ‚Â f. sp.Ã‚Â lycopersici